Penguatan reformasi birokrasi di pemerintah Provinsi Jawa Timur dalam perspektif policy leadership - Suhartono Winoto; Marina Tri Handayani (Publisia: Jurnal Ilmu Administrasi Publik, 2022)
Bureaucratic reform is a way out in realizing a better bureaucracy as well as a solution to problems in public services. This study aims to demonstrate and analyze efforts to strengthen bureaucratic reform through the perspective of policy leadership carried out by the East Java Provincial Government under the leadership of Khofifah Indar Parawansa as the Governor of East Java Province. Policy leadership itself refers to four important aspects, namely commitment to bureaucratic reform, initial allocation of resources, support from legislators, and reform management models. In this study, the author explores and analyzes related to efforts to strengthen bureaucratic reform in the East Java Provincial Government through descriptive qualitative approaches and case studies as research methods. Data collection was carried out through extracting data and information contained in the East Java Provincial Medium-Term Development Plan for the 2019-2024 period and the Instagram social media platform of the East Java Organizational Bureau. The results of this study indicate that the East Java Provincial Government's seriousness in pursuing bureaucratic reform can be seen from the perspective of policy leadership. First, the strong commitment of Khofifah Indar Parawansa as the Governor of East Java Province, as well as his subordinates. Second, optimizing the allocation of existing resources which is realized through bureaucratic reform programs and activities. Third, the role of legislators is to form a support system. Finally, the reform management model is used as a reference in implementing bureaucratic reform in the East Java Provincial Government.